Importance–Performance Analysis (IPA) of Foodservice Operation, Dietary Life Education, and Nutrition Counseling Tasks of Nutrition Teachers and Dietitians in Jeju, Korea - Eun A Park (Nutrients, 2017)
The purpose of this study was to analyze foodservice operation, dietary life education, and nutrition counseling tasks of nutrition teachers and dietitians in elementary, middle, and high schools in Jeju, Korea, and to provide effective ways to implement dietary life education and nutrition counseling in schools. This study surveyed 94 nutrition teachers and 46 dietitians working at elementary, middle, and high schools in Jeju during 7–14 May 2015. The importance and performance of 16 tasks of nutrition teachers and dietitians were measured using questionnaires. The data was analyzed by using the SPSS software and Importance–Performance Analysis (IPA). Importance was ranked in the order of foodservice operation (4.72), dietary life education (4.37), and nutrition counseling (4.24); and performance was ranked in the order of foodservice operation (4.48), dietary life education (3.70), and nutrition counseling (3.22). The importance–performance matrix showed that in Quadrant 4, the “Concentrate Here” item was “nutrition and dietary life education for students”, while in Quadrant 2, the “Possible Overkill” item was “cost control and office management”. These findings suggest that it is important to reduce unnecessary administrative and office management tasks in order for nutrition teachers and dietitians to implement effective nutrition education, dietary life education, and nutrition counseling programs.